SOCIAL INTELLECT IN THE SYSTEM OF PERSONALITY PSYCHOLOGICAL CHARACTERISTICS: RESULTS OF CLUSTER ANALYSIS (on the example of future programmers) (Psychology Travelogs, 2025)
The article presents the results of an empirical study aimed at identifying the structural organization and key psychological determinants of social intelligence in future programmers. Social intelligence is considered as a multidimensional construct that integrates cognitive processing of social information, emotional regulation, interpersonal sensitivity, and behavioural adaptability. These components jointly determine the effectiveness of communication, cooperation and professional interaction in the IT environment, which is characterized by high cognitive demands, teamwork, dynamic social contexts and increased emotional load.The empirical study examined the interrelations between personality traits, emotional stability, self-regulation, and indicators of social adaptability among students of IT specialities. Using multivariate statistical procedures, including hierarchical cluster analysis, several stable clusters were identified, reflecting different levels of social functioning: socio-psychological maturity, cognitive-personal integration, moral-volitional regulation, emotional dynamics, emotional disharmony and interpersonal adaptation. A higher-order cluster representing personal integrity was revealed, indicating the systemic interconnection between cognitive, emotional and volitional components of social intelligence.The results demonstrate that social intelligence of future programmers functions as an integrated psychological system in which intellectual flexibility, emotional balance, self-acceptance, moral responsibility and social awareness interact to ensure constructive communication and effective teamwork. The findings broaden the understanding of the psychological structure of social intelligence and highlight its importance for professional training in the IT field. They also create a foundation for developing educational and psycho-corrective programmes aimed at strengthening socio-emotional competencies and supporting professional development of future IT specialists.
Keywords: social intelligence; IT specialists; future programmers; self-regulation; emotional stability; adaptability; socio-psychological maturity; social competence; moral-volitional regulation; interpersonal interaction; cluster analysis